Nocturia: consequences, classification, and management - Fine, Noam D. (F1000Res, 2017)
Nocturia is a widespread condition that can negatively impact quality of sleep and overall health. This condition is multifactorial in nature and is best approached through the analysis of frequency volume charts. Through these charts, clinicians may classify each individual case of nocturia into one of four distinct categories: global polyuria, nocturnal polyuria, reduced bladder capacity, and mixed. Treatments should then be tailored to each individual based upon the category of their nocturia. In some cases, appropriate therapy will consist of behavioral modification techniques or addressing underlying systemic diseases. In other cases, medical therapy may be necessary, but, to date, medications have shown limited efficacy at treating nocturia.